Genetic resistance to Fusarium wilt shapes rhizospheric beneficial microbiota in four banana cultivars - Troya, Cristina M.; Mendes, Lucas W.; Costa, Marileide M.; Rigobelo, Everlon Cid [UNESP]; Pfenning, Ludwig H.; Buttros, Victor Hugo; Dória, Joyce (Elsevier, 2024)
This study explores the dynamics of bacterial communities in the bulk soil, rhizosphere, and endosphere of banana plants, focusing on variations among cultivars with differing levels of genetic resistance to Fusarium wilt. Four banana cultivars were examined: one resistant (P), one moderately susceptible (PT), and two susceptible (W and M). Using 16S rDNA sequencing, we analyzed the bacterial community structures in these habitats. Results showed significant differences in bacterial communities across the three habitats and among the cultivars, with the endosphere communities being the most distinct. The rhizosphere and bulk soil communities exhibited more similarities, likely due to the soil microbiome's influence on the rhizosphere. Resistant cultivars (PT and P) displayed unique bacterial communities, with notable taxa such as Burkholderia, Leifsonia, and Marmoricola in the rhizosphere, known for their antagonistic properties against Fusarium oxysporum. Although the most abundant taxa are not the only ones influencing disease suppression, the susceptible cultivars (W and M) were dominated by genera such as Reyranella and Mucilaginibacter, which are yet to be described as potential biocontrol agents against Fusarium wilt. The endosphere of resistant cultivars also featured beneficial genera like Amycolatopsis and Achromobacter, known for their roles in plant growth promotion and disease resistance. The findings underscore the importance of plant genotype and soil type in shaping the rhizosphere microbiome, with specific microbial taxa associated with resistance to Fusarium. These insights suggest a potential for developing targeted microbial-based strategies to enhance disease resistance and overall plant health. The study highlights key microbial players that could be leveraged for biological control and improved management of Fusarium wilt in banana cultivation. This research advances our understanding of plant-microbe interactions and their implications for sustainable agriculture, particularly in combating soilborne pathogens.
Keywords: 16S rDNA; Bacterial diversity; Fusarium wilt; Musa spp.; Panama disease; Rhizosphere